Application of Biophosphate fertilizer on Peanut (Arachis hypogeae L) in Lowland - Rosmiah Rosmiah; Neni Marlina; Berliana Palmasari; Ida Aryani; Gamal Abd. Nasser (Journal of Global Sustainable Agriculture, 2024)
The lowland has the potential to be utilized for agriculture, such as planting peanuts, even though the soil fertility level is not very supportive The use of bio-phosphate fertilizers containing phosphate-solubilizing bacteria can be utilized to help improve the soil and contribute to nutrient elements The advantages of bio-phosphate fertilizers include protecting roots from Fusarium infect, optimizing inorganic fertilizers, and increasing peanut production This research was conducted in Pulau Semambu Village, Inderalaya Utara, Ogan Ilir Palembang from October 2023 to January 2024. The experimental layout used a non-factorial randomized block design with 6 treatments repeated 4 times The treatment factors included biofosfat fertilizer (B), namely B1 = 25 kg/ha, B2 = 50 kg/ha, B3 = 75 kg/ha, B4 = 100 kg/ha, B5 = 125 kg/ha, B6 = 150 kg/ha (B)